2010
DOI: 10.1111/j.1365-2850.2009.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing unplanned care teams in Scotland: evaluating outcomes

Abstract: Mental health nursing, along with other professional groups, has had to adapt to new ways of delivering health services, often in response to government policy. Consequently, traditional professional boundaries and roles are being rapidly and consistently expanded, often requiring coordinated responses across strategic, educational and clinical domains to ensure service users experience high-quality mental health interventions. This paper explores and evaluates such a coordinated response in developing unplann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In order to maximize the information gathered and to ensure that details about all three aspects are captured, information is usually gathered using qualitative approaches, such as interviews or focus groups. Semi-structured interviews (Kennedy, Rogers, & Gately, 2005), a reflexive critical discourse (Hurley, Kelly, Mears, Morrison, & Wiseman, 2010), or a co-created dialogue (as recommended by Pawson & Tilley, 1997) have been used. Fisher and Downes (2008) used a Delphi consultation process with a wide group of stakeholders to generate and validate a set of initial scenarios representing mid-range theories.…”
Section: Introductionmentioning
confidence: 99%
“…In order to maximize the information gathered and to ensure that details about all three aspects are captured, information is usually gathered using qualitative approaches, such as interviews or focus groups. Semi-structured interviews (Kennedy, Rogers, & Gately, 2005), a reflexive critical discourse (Hurley, Kelly, Mears, Morrison, & Wiseman, 2010), or a co-created dialogue (as recommended by Pawson & Tilley, 1997) have been used. Fisher and Downes (2008) used a Delphi consultation process with a wide group of stakeholders to generate and validate a set of initial scenarios representing mid-range theories.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the scope, effectiveness and impact of policies and programs to promote health including the appropriate use of assessment and research methods to support improvement in programs, sustainability and dissemination (15) . Research on the roles of the expanded practice of community mental health nurses indicated that they were less confident about prescribing, even though, more than half (54%) reported that they definitely or Evaluates the coordinated response in development of unplanned care services for mental health (8) Identifies confidence and preparation of community mental health nurses when performing expanded roles (9) Identifies cultural factors that contributed to substance abuse in adolescents (10) Explores how mental health workers and respond to women who reveals sexual abuse in the scenario of crisis service (11) Professionals identify cultural barriers of women in attendance (11) Managing and negotiating health care delivery systems nurse practitioner-patient relationship teaching/coaching Function Analyzes the extent of mental health services provided to families (12) On the significance of the relationship with the patient, highlights the genuine partnership and confidence (13) Unidentified probably felt confident to prescribe medication. More than 90% said they probably or definitely felt confident in making recommendations for involuntary treatment, 84% and 79% showed similar levels of confidence in ordering of diagnostic tests and in referring patients to specialist physicians, respectively (9) .…”
Section: Discussionmentioning
confidence: 99%
“…First, professionals' competencies were recognized and abilities needed to be strengthened in order to provide effective responses to the needs of the service user of mental health. In a second moment, an educational training was applied for mental health nurses to prepare them to take on key roles and responsibilities in the service, which was reflected in a highly positive learning experience for most participants, with indications of relevant learning to be achieved for clinical practice (8) . The project contributed to the development of competence in the field of monitoring and ensuring the quality of health care practice, when sought to interpret their own professional forces, the role and scope of peers ability, using assessment information to improve care and practice and monitor the quality of their own practice and participate in continuous quality improvements (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation